f-Sim EON: Performance Evaluation in Elastic Optical Networks Under Cascading Failures - Santos, Eonassis O.; Richa, Carlos S. G.; Santos, Alex S.; Santi, Juliana de; Rocha, Antonio A. A.; Figueiredo, Gustavo B. (Companion Proceedings of the Brazilian Symposium on Computer Networks and Distributed Systems (SBRC); 2024: Companion Proceedings of the 42nd Brazilian Symposium on Computer Networks and Distributed SystemsDO - 10.5753/sbrc_estendido.2024.3340, 2024)
The article introduces the f-Sim EON simulator, developed to investigate the impacts of cascading failures in Elastic Optical Networks (EON). Implemented in Python 3 using the SimPy library, the simulator allows modeling various failure scenarios and evaluating risk mitigation strategies. Composed of modules, f-Sim EON offers a flexible platform for analysis and optimization of EONs in dynamic environments, promoting advancements in understanding and resilience of EONs.